The Invisibility of Women's Organizations in Decision Making Process and Governance in Nigeria - Afolabi, Comfort Yemisi (Frontiers in Sociology, 2019)
The exciting development in the recent political era was the increase in women's political participation globally. Women are becoming more engaged in varieties of institutional decision making processes and Africa appears to be leading in women's parliamentary representation. Since the re-birth of democracy in Nigeria in 1999, women have tried to gain access to decision making positions by contesting at various political levels and the representation of women's organizations on various policy debates has increased at local and national levels. However, their efforts appeared not to be greeted with much gains as the result seemed not very encouraging. What is problematic is whether the representation of women's organization in democracy and decision making in Nigeria was descriptive or substantive. Even when women's organizations were represented in decision making arena, it appeared that their influence was not much felt. Therefore, this paper investigated how visible and substantive were the roles played by women's organizations in decision making arena in Nigeria and whether their roles were appreciated. The paper utilized the descriptive survey research design to elicit and describe information. The findings revealed that the roles played by women's organizations in decision making arena was significant but not visible and unappreciated. It was therefore, recommended that women's organizations should do all they could to be more active in governance and encourage more women to be fully involved in decision making process in Nigeria to enhance national development.